Positioning the World Bank. - Gilbert, C; Powell, A; Vines, D (1999)
This article examines the rationale for the World Bank and explores whether its objective is best served by its current mix of activities. We are critical of the Bank's reliance on conditionality, and advocate evolution into a Knowledge Bank, which would lend with few conditions to countries with good policies and good institutions, and would concentrate on the provision of knowledge and technical assistance, rather than lending, in countries where the policy framework is poor. We also advocate an expansion in the Bank's role as a provider of global public goods; we critically examine the Banks role in relation to financial crises.